ANZAC girls [videorecording (DVD)] - Flood, Georgia; Brent, Laura; Prebble, Antonia; McGahan, Anna (Screentime Pty Ltd, 2014)
Based on true events, this uplifting drama tells the story of five Australian and New Zealand nurses during World War I. Drawing on the real participants' diaries and letters, this six-part drama celebrates the contributions of women to the war effort.